Quantitative and Qualitative Analysis of Antibiotics in the Intensive Care Unit (ICU) - Mareta Rindang Andarsari; Lisa Ariyanti Zainu; Sri Rahayu Saleh; Aminatush Sholichah; Dewi Wara Shinta; Cahyo Wibisono Nugroho (Jurnal Sains dan Kesehatan, 2023)
The high incidence of infection in the ICU requires frequent use of antibiotics, thereby increasing the risk of developing antibiotic resistance when used irrationally. To assess the quantity and quality of antibiotic use, the World Health Organization (WHO) recommends using the Anatomical Therapeutic Chemical (ATC) classification system or the Defined Daily Dose (DDD) method. In that study, 25 articles were analyzed, including 21 quantitative research articles and four qualitative research articles. These articles were obtained from three databases: PubMed Central (PMC), Research Gate, and Google Scholar. The most commonly used antibiotics in the ICU are ceftriaxone (1×2g, IV) with a DDD value of 358,139/100 bed-days, meropenem (3×2g, IV) with a DDD value of 289,747/100 bed-days, and piperacillin-tazobactam (4×4.5g, IV) with a DDD value of 164,816/100 bed-days. These values indicate the number of antibiotics used in relation to 100 days of sleep. In addition, evaluation of the quality of antibiotic use in the ICU revealed that it is generally characterized by irrational use. By conducting such research, healthcare professionals can optimize the use of antibiotics in the ICU, leading to more effective treatment outcomes while minimizing the development of antibiotic resistance. Keywords: Antibiotics, ATC/DDD, Gyssens, intensive care unit